All in One High Quality Genomic DNA and Total RNA Extraction From Nematode Induced Galls for High Throughput Sequencing Purposes - Silva, Ana Cláudia; Ruiz-Ferrer, Virginia; Martínez-Gómez, Ángela; Barcala, Marta; Fenoll, Carmen; Escobar, Carolina (Frontiers in Plant Science, 2019)
Meloidogyne spp. are plant-parasitic nematodes that form a very complex pseudo-organ, called gall, which contains the giant cells (GCs) to nourish them. During the last decade, several groups have been studying the molecular processes accompanying the formation of these structures, combining both transcriptomics and cellular biology. Among others, it was confirmed that a generalised gene repression is a hallmark of early-developing GCs formed by Meloidogyne javanica in Arabidopsis and tomato. One of the main mechanisms behind this gene repression involve small RNAs (sRNAs) directed gene silencing. This is supported not only by the described action of several microRNAs differentially expressed in galls, but to the differential abundance of 24-nucleotide sRNAs in early developing Arabidopsis galls, particularly those rasiRNAs which are mostly involved in RNA-directed DNA methylation. Their accumulation strongly correlates to the repression of several retrotransposons at pericentromeric regions of Arabidopsis chromosomes in early galls. However, the contribution of this global gene repression to GCs/galls formation and maintenance is still not fully understood. Further detailed studies, as the correlation between gene expression profiles and the methylation state of the chromatin in galls are essential to raise testable working hypothesis. A high quality of isolated DNA and RNA is a requirement to obtain non-biased and comprehensive results. Frequently, the isolation of DNA and RNA is performed from different samples of the same type of biological material. However, subtle differences on epigenetic processes are frequent even among independent biological replicates of the same tissue and may not correlate to those changes on the mRNA population obtained from different biological replicates. Herein, we describe a method that allows the simultaneous extraction and purification of genomic DNA and total RNA from the same biological sample adapted to our biological system. The quality of both nucleic acids from Arabidopsis galls formed by M. javanica was high and adequate to construct RNA and DNA libraries for high throughput sequencing used for transcriptomic and epigenetic studies, such as the analysis of the methylation state of the chromatin in galls (MethylC-seq) and RNA sequencing (RNAseq). The protocol presents guidance on the described procedure, key notes and troubleshooting.